Auditor independence in Kinship economies: a MacIntyrian perspective - Pimentel, Erica (Journal of business ethics, 2023)
This paper explores the practices of auditors in a non-Western cultural environment. Drawing on Alasdair MacIntyre's virtue ethics framework and narrative interviews with twenty Tunisian auditors, we investigate how auditors reconcile their duty to independence with the expectations of a kinship economy. Additionally, we explore how institutions-such as professional oversight bodies-play into this reconciliation. We find that, although auditors may pursue a telos at odds with international auditing standards, the purpose that these auditors serve is congruent with their moral tradition. That is, rather than positioning themselves as objective arbiters of financial reporting, these auditors position themselves as guardians of their auditees. While this revised position engenders conduct that may appear to violate their independence, our auditors' practices are congruent with the virtues of justice, courage, and honesty, as they conceive of them in the context of a Tunisian moral tradition. This study makes two main contributions to the literature. First, we provide empirical evidence into the ways in which auditors redefine independence in the context of a kinship economy. Second, we demonstrate that, when auditing local firms, auditors apply a version of professionalism that emphasizes community-oriented care over objectivity.